Educação rural no município de Araucária/PR: de escolas isoladas a escolas consolidadas - Tibucheski, Jaqueline Kugler (2012)
The rural education in Brazil was introduced in the educational legislation in the second half of the twentieth century. Historically, its political and pedagogical organization followed urban society logic. Its schools were institutionalized as isolate, multigrade teaching and single teacher schools. Since the 1970s Brazil has managed on projects of implementation or nucleation of rural schools. Such nucleation politics caused the closing of innumerable schools. The maintenance, closing or nucleation of the rural schools was always a matter of government decision, taking into account the number of students enrolled. In this research the object of study was the consolidation process of the schools situated in the rural area of Araucaria, a city in the metropolitan area of Curitiba. Araucaria had six rural schools in 2011. The objectives of this research were to analyze how the nucleation process occurred in those schools, how was the relationship between community and municipal government and identify the main changes occurred in the organization and teaching practice in those schools. In order to achieve those endings a qualitative research approach was used, using a document analysis and focusing on the consolidation process of the rural schools. The main data collection techniques were: observation and field notes, and teachers' interview as well as community members and educational administrators who had experienced the consolidation process of the schools, at the state or municipal level. The research's theoretical foundation is based on authors of history of education and school institutions, especially those who devote attention to researching rural schools in Brazil. The research shows that the rural schools, despite having specific characteristics, have been planned without considering the students' learning process peculiarities. The consolidation politic of the rural schools was an attempt to create opportunities for rural areas students to have access to an education of equal quality to urban schools. The research's results show that changes occurred in different fronts, namely: school transport, school meals, teaching planning and, teacher-student relationship.